Interpretations of aeromagnetic data over lokoja and environs, Nigeria - Chinwuko, Augustine; Ojonugwa, Usman; Onwuemesi, Ajana; Anakwuba, Emmanuel; Okonkwo, Churchill; Ikumbur, Emmanuel (International Journal of Advanced Geosciences, 2014)
Total field aeromagnetic anomalies over Kogi-Auchi area have been evaluated in order to map the magnetic lineaments and estimate the depth to basement (sedimentary thicknesses). Aeromagnetic and radiometric data of the area (sheet 246, 247, 266 and 267) were acquired, digitized and analyzed. The slope methods were applied in the analysis of the residual contour map. The result obtained using the slope methods reveals two depth sources in the study area; on the average the deeper magnetic sources range from 2.3 to 4.9 km, while the shallower magnetic sources range from 1.1 to 1.6 km. These shallower sources are probably due to the presence of igneous intrusives and/or magnetized bodies within the sedimentary cover. Visual study of the residual anomaly map shows the presence of igneous intrusive in the entire North and Southwestern part of the study area. The One Vertical Derivative (1VD) lineament map shows the Fault trending in Northwest-Southwest (NW-SW) and Northeast-Southwest (NE-SW) direction and this conforms to the Niger-Benue basin itself. Hydrocarbon exploration is not recommended since the area has low thickness of sediment on the average. All this deduction were reached after due consideration of qualitative and quantitative interpretations supported by geological information of the area. Keywords: Aeromagnetic Data, Radiometric Data, Lineament, Igneous Intrusives, Depth to Basement.